2010
DOI: 10.1242/dev.052225
|View full text |Cite
|
Sign up to set email alerts
|

Hand2 ensures an appropriate environment for cardiac fusion by limiting Fibronectin function

Abstract: SUMMARYHeart formation requires the fusion of bilateral cardiomyocyte populations as they move towards the embryonic midline. The bHLH transcription factor Hand2 is essential for cardiac fusion; however, the effector genes that execute this function of Hand2 are unknown. Here, we provide in zebrafish the first evidence for a downstream component of the Hand2 pathway that mediates cardiac morphogenesis. Although hand2 is expressed in cardiomyocytes, mosaic analysis demonstrates that it plays a non-autonomous ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 31 publications
(28 reference statements)
4
70
0
Order By: Relevance
“…The midline expression of fli1a, kdrl, cdh5 and etv2:GFP in endocardial progenitors was largely unaffected in hand2 mutants at the 17-somite stage (Fig. 1I-L), in agreement with previous studies (Garavito-Aguilar et al, 2010). To visualize endocardial development during the stages of the cone formation, we analyzed endocardial and myocardial formation in double-transgenic etv2: GFP; myl7:mCherry embryos at 22-36 hpf.…”
Section: Hand2 Is Required Within the Myocardium For Endocardial Diffsupporting
confidence: 89%
See 2 more Smart Citations
“…The midline expression of fli1a, kdrl, cdh5 and etv2:GFP in endocardial progenitors was largely unaffected in hand2 mutants at the 17-somite stage (Fig. 1I-L), in agreement with previous studies (Garavito-Aguilar et al, 2010). To visualize endocardial development during the stages of the cone formation, we analyzed endocardial and myocardial formation in double-transgenic etv2: GFP; myl7:mCherry embryos at 22-36 hpf.…”
Section: Hand2 Is Required Within the Myocardium For Endocardial Diffsupporting
confidence: 89%
“…Previous studies have demonstrated that endocardial precursors in hand2 mutants migrate to the midline and form the endocardial sheet similar to their wild-type siblings but exhibit defective antero-posterior spreading (Garavito-Aguilar et al, 2010). However, endocardial differentiation has not been previously analyzed in hand2 mutants.…”
Section: Hand2 Is Required Within the Myocardium For Endocardial Diffmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Tmem2 could act to limit the activity of inductive signals that specify AVC endocardium; for example, the similarities between frv mutants and apc mutants suggest a possible role of Tmem2 in restricting Wnt signaling (Hurlstone et al, 2003;Verhoeven et al, 2011). During cardiac fusion, Tmem2 might facilitate the transduction of an unknown myocardial-to-endocardial motility cue; however, this scenario seems unlikely because the endocardium can move to the midline in hand2 mutants, which possess very few cardiomyocytes (Garavito-Aguilar et al, 2010). Alternatively, rather than influencing specific signaling pathways, Tmem2 might impact myocardial and endocardial morphogenesis by modulating the extracellular environment.…”
Section: Tmem2 Is Essential For the Coordination Of Myocardial And Enmentioning
confidence: 99%
“…Additionally, either diminished or excessive deposition of extracellular matrix (ECM) can hinder myocardial and endocardial movement (e.g. Arrington and Yost, 2009;Garavito-Aguilar et al, 2010;Trinh and Stainier, 2004). Furthermore, the myocardium and endocardium may impact the behavior of one another.…”
Section: Introductionmentioning
confidence: 99%